PREVENTIVE SETTLEMENT AS A PREVENTIVE MEANS TO SAFEGUARDING TROUBLED BUSINESSES FROM BANKRUPTCY: AN ANALYSIS OF THE UAE LAW (Lex localis - Journal of Local Self-Government, 2025)
This study explores the legal framework surrounding the preventive settlement method and its potential to mitigate bankruptcy risks for troubled commercial enterprises. It enables debtors in financial distress to petition the competent court for protection, helping them avoid default and bankruptcy proceedings. The research employs qualitative and analytical approaches, focusing on the UAE Financial Restructuring and Bankruptcy Law No. 51 of 2023 (FRBL) and relevant case law. The findings indicate that preventive settlement procedures facilitate creditors in recovering their dues, which has a positive impact on the national economy. Consequently, the study recommends incorporating Article 57 FRBL, a requirement that mandates the debtor to include a proposal for paying off a portion of their debts in the application for a protective settlement, along with a specified timeline for these payments, as a prerequisite for accepting the settlement application. The study also recommends that the debtor provide evidence of not being convicted of any offenses outlined in FRBL when seeking a preventive settlement. This measure ensures the debtor's good faith in the application process.